2015
DOI: 10.1007/s00784-015-1680-4
|View full text |Cite
|
Sign up to set email alerts
|

Healing of localized gingival recessions treated with a coronally advanced flap alone or combined with an enamel matrix derivative and a porcine acellular dermal matrix: a preclinical study

Abstract: The present results suggest that the combination of EMD and PADM in conjunction with CAF may represent a promising approach for treating single Miller class II gingival recessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 49 publications
10
32
1
Order By: Relevance
“…58,59 Therefore, PADM serves as a threedimensional (3D) matrix, promoting the proliferation of fibroblasts and endothelial cells and supporting a fast revascularization of its structure. 58,59 Therefore, PADM serves as a threedimensional (3D) matrix, promoting the proliferation of fibroblasts and endothelial cells and supporting a fast revascularization of its structure.…”
Section: Xenogeneic Acellular Dermal Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…58,59 Therefore, PADM serves as a threedimensional (3D) matrix, promoting the proliferation of fibroblasts and endothelial cells and supporting a fast revascularization of its structure. 58,59 Therefore, PADM serves as a threedimensional (3D) matrix, promoting the proliferation of fibroblasts and endothelial cells and supporting a fast revascularization of its structure.…”
Section: Xenogeneic Acellular Dermal Matrixmentioning
confidence: 99%
“…58,59 Therefore, PADM serves as a threedimensional (3D) matrix, promoting the proliferation of fibroblasts and endothelial cells and supporting a fast revascularization of its structure. 59 Figure 4 showed two clinical cases in which PADM was used for the treatment of soft tissue deficiencies at tooth and implant sites. 59 Figure 4 showed two clinical cases in which PADM was used for the treatment of soft tissue deficiencies at tooth and implant sites.…”
Section: Xenogeneic Acellular Dermal Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vitro study has shown good biocompatibility for PADM with regard to endothelial progenitor cells (EPC), and reflects high EPC viability and migration ability without any cytotoxic or apoptotic effects on the investigated progenitor cell lineage . This PADM can promote growth and proliferation of human gingival fibroblasts, osteoblasts, and endothelial cells in vitro while in vivo findings have revealed that PADM is capable of significant revascularization of its collagen structure during the early healing period …”
Section: Introductionmentioning
confidence: 97%
“…13 This PADM can promote growth and proliferation of human gingival fibroblasts, osteoblasts, and endothelial cells in vitro 13,14 while in vivo findings have revealed that PADM is capable of significant revascularization of its collagen structure during the early healing period. 15 A very recent case series has evaluated the outcomes in twelve patients presenting at least two adjacent Miller Class I or II gingival recessions treated with MCAT in conjunction with PADM and shown that this procedure may be clinically successful. 16 Overall, the available data appear to suggest that this newly developed PADM might represent an alternative to CTG, thus warranting further investigation particularly when treating cases of multiple adjacent gingival recessions.…”
mentioning
confidence: 99%